Evaluation of evidence value of car primer using pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS) and chemometrics / Raja Zubaidah Raja Sabaradin and Rozita Osman - Raja Sabaradin, Raja Zubaidah; Osman, Rozita (Faculty of Applied Sciences, 2021)
The car paint system consisted of four different layers; namely cathodic electrodeposition (CED), primer, the basecoat, and clear coat. Each of these layers may offer valuable information in an analysis of car paint. However, the recovery of a small amount of car paint from a crime scene may not consist of all four layers. Thus, this study is conducted to evaluate the evidence value of car primer in the presence of basecoat and absence of clear coat. In this study, 80 car paint samples, consisting of eight different red basecoats and ten types of primers were analyzed using Py-GCMS to evaluate the contribution of the primer layer in the analysis of car paint sample. The chromatographic dataset obtained was subjected to chemometric techniques namely principal component analysis (PCA) and cluster analysis (CA). 22 principal components were rendered from PCA with a total variance of 81.23%. CA's three clusters are cluster 1 and 3 which was based on the shades of red basecoat while cluster 2 was based on the type of primer. This observation showed that the car primer might have a significant contribution to the analysis of car paint using Py-GC-MS.